Endocytosis of exogenous factor V by ex‐vivo differentiated megakaryocytes from patients with severe parahaemophilia. (22nd July 2016) - Radu, Claudia M.; Spiezia, Luca; Bulato, Cristiana; Gavasso, Sabrina; Campello, Elena; Sartorello, Francesca; Castoldi, Elisabetta; Simioni, Paolo
Summary: Although human megakaryocytes can synthesize factor V (FV), platelet FV derives largely from endocytosis of plasma FV. Recently, it has been shown that plasma transfusions can replenish the platelet FV pool in parahaemophilic patients. Here we corroborate this finding by showing FV endocytosis by ex vivo differentiated megakaryocytes derived from patients with inherited parahaemophilia. Mononuclear stem cells isolated from peripheral blood of healthy subjects and of three patients with severe parahaemophilia were cultured in the presence of thrombopoietin and interleukin‐3 and differentiated into CD41‐positive polynucleated megakaryocytes. Exogenous purified FV was added to the culture medium to evaluate FV endocytosis. Immunofluorescence staining revealed abundant FV expression in megakaryocytes derived from healthy donors, but no FV expression in those derived from patients with severe parahaemophilia. However, after the addition of purified FV to the culture medium, megakaryocytes from parahaemophilia patients became positive upon FV immunostaining, suggesting endocytosis of exogenous FV. Endocytosed FV retained factor Xa‐co‐factor activity as assessed by a prothrombin time‐based functional test in megakaryocyte lysates. Addition of exogenous FV to culture medium can restore the FV content of megakaryocytes derived from patients with severe FV defects. This rescue mechanism can have important clinical implications in the management of parahaemophilia patients.